Reporting Gender Pay Gaps in OECD Countries Guidance for Pay Transparency Implementation, Monitoring and Reform (Gender Equality at Work, 2023)
Pay transparency policies are gaining momentum throughout the OECD. Over half of OECD countries require private sector firms to report their gender pay gap statistics regularly to stakeholders like employees, employee representatives, the government, and/or the public. Gender pay gap reporting, equal pay audits and other pay transparency policies help advance gender equality at the workplace, as these measures present up-to-date information on a firm's gender pay gap, encourage employers to offer equal pay for work of equal value, and give individual workers and their representatives valuable insights to fight for pay equity. This report presents the most thorough stocktaking to date of gender pay gap reporting policies and evaluations across OECD countries, and offers guidance to countries interested in introducing, reforming and monitoring their pay transparency systems to promote equal pay for women and men